THE INVESTMENT OPPORTUNITY AND COMPANY SIZE AFFECTING FINANCIAL PERFORMANCE AND DIVIDEND POLICY - Putra, Gede; Manuari, Ida (JRAK, 2024)
Investment is no longer limited to the upper class; it now includes participation from the lower middle class as well. This research was conducted at the Indonesia Stock Exchange with a sample size of 45. The sample comprised 15 companies with a three-year observation period. Based on the outcomes of this research, researchers can draw the following conclusions: Investment Opportunity Set (IOS) and firm size exhibit a positive influence on financial performance. However, company performance also serves as a mediator in the relationship between firm size and its impact on dividend policy. The practical implication for investors is to take into account variables that have been demonstrated to influence dividend policy when making investment decisions, with the aim of maximizing profits from dividends. For companies, it is essential to recognize that these variables, particularly the allure of dividends, can become a compelling attraction for the company itself.